Lumps and swellings of the salivary glands 2 - Langdon, John D. (Henry Stewart Talks, 2017)
Management of salivary neoplasms, Swelling of the salivary glands due to neoplasms, degenerative conditions and sialosis and age changes, Clinical appearances of the different causes of swelling